The Indian in the cupboard - Banks, Lynne Reid, 1929-; Cole, Brock (New York : Doubleday, 1980)
A nine-year-old boy receives a plastic Indian, a cupboard, and a little key for his birthday and finds himself involved in adventure when the Indian comes to life in the cupboard and befriends him.
780
Accelerated Reader AR
Keywords: Indians of North America -- Fiction; Toys -- Fiction; Magic -- Fiction; Fantasy fiction